Factors Influencing Audit Delay - Ramadhan, Alif Rizki; Saraswati, Erwin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Timely financial information allows management to make quick and accurate business decisions. Delays in financial reports can lead to decisions based on data that is not up-to-date and have negative consequences for the company. Understanding the factors that influence the delay in submitting financial reports is very important to improve efficiency in making business decisions. This study aims to test and obtain empirical evidence regarding factors that affect audit delay as seen from company size, solvency, KAP size, and audit committee. This study uses data from 100 non-primary consumer goods companies listed on the IDX for the 2020-2022 period, which are determined using a purposive sampling method with data collection techniques using the archival method, which is carried out by collecting financial reports from each sample company. Furthermore, the data analysis technique used is multiple linear regression analysis. This study supports the signaling theory that company size and audit committees have a decreased effect on audit delay, and solvency has an increased effect on audit delay. This study has not been able to prove the relationship between KAP size on audit delay. This study recommends that auditors conduct audits effectively and efficiently so as to reduce audit delay. Regulators impose strict sanctions on companies that are late in issuing financial reports in order to create a deterrent effect.